Indices de atividade da doença inflamatória do intestino: indicadores clínicos e laboratoriais. - Dichi, I.; Burini, Roberto Carlos [UNESP] (My University, 1995)
The quantification of the degree of activity of inflammatory bowel disease is assuming growing importance nowadays. The activity index of the disease can be attained by clinical and laboratorial indicators. For ulcerative colitis the mostly used clinical parameters are daily bowel movements and presence of bloody diarrhea whereas albumin, hemoglobin, ESR and positive acute phase protein measurements are the laboratory parameters. For Crohn's disease activity besides the daily bowel movements the presence of abdominal pain and discomfort sensation are also frequently used whereas the C-reactive protein is the most used laboratory test which is able to detect the disease reactivation even before the appearance of any clinical sign. The combinations of clinical signs with the laboratory tests earned the sympathy of the specialists and the set of ensembled indicators has been recognized by the author's name. In this sense, the classification of the ulcerative colitis activity originally proposed by Truelove and Witts deserves presently a wide acceptance whereas such agreement is still lacking for Crohn's disease activity. In the mean time, the Bristol index is clinically the most feasible, once the Crohn's disease activity index and the Van Hees index are considered too complex. However the latter indexes are still useful mainly for comparisons among multicentric data. It seems that the currently existing clinical signs used for Crohn's disease activity would be quantitatively improved by adding some easily made laboratory tests such as C-reactive protein.
Inflammatory bowel disease activity index: clinical and laboratory indicators
Keywords: age; Crohn disease; enteritis; female; hospitalization; human; male; review; ulcerative colitis; Age Factors; Colitis, Ulcerative; Crohn Disease; Female; Humans; Inflammatory Bowel Diseases; Male; Severity of Illness Index